Using in-house 3D technology for optimal spatial positioning of elongation devices for distraction osteogenesis—a cost-effective alternative - Rachmiel, Adi; Shilo, Dekel; Hija, Ahmad; Capucha, Tal; Zeineh, Nidal; Emodi, Omri; Krasovsky, Andrei (Frontiers in Oral Health, 2025)
IntroductionMandibular distraction osteogenesis is globally accepted as the gold-standard surgical solution for various craniofacial deformities and syndromes. Stock device evolution has advanced into complex designs to achieve the most accurate three-dimensional distraction vector of elongation. Today's cutting-edge solution is patient-specific distractors designed by virtual surgical planning (VSP) to facilitate surgical performance and ensure the most predictable clinical results. However, tailoring patient-specific distractors comes with a significant price tag.MethodsUsing VSP technology, we developed an inexpensive stepwise method of precisely directing the distraction vector by adapting off-the-shelf distractors for the individual contour of the patients’ mandibles based on the in-house designed and printed cutting guides.ResultsThe virtual planning sequence and clinical application are described in detail. The final results are assessed by 3D analysis to confirm the method's precision and predictability.DiscussionThe final positions of the adapted off-the-shelf distractors were found to match the pre-operative virtual planning precisely, resulting in excellent clinical results. This method can be easily reproduced in similar clinical cases with reduced cost.